Planned surveys - Mills, Vicente; Philippines. Bureau of lands; Philippines(Commonwealth). Bureau of lands (Manila Bureau of Printing, 1937)
Deals with cadastral survey carried out by the Bureau of lands of under its supervision, 1901-1937, and includes estimates of the time and cost involved in completing such surveys of the whole territory of the commonwealth.
Available in microfilm at ISAIS Section see accession number (MCF-7593)
Keywords: Real property -- Philippines; Philippines -- Surveys